158k views
4 votes
Make w the subject of the formula y-aw=2w-1

2 Answers

5 votes

w( a + 2)= 1 + y → ( divide both sides by (a + 2 ) )

w = \frac{1 + y}{a + 2}

User Ziul
by
4.9k points
0 votes

w =
(1 + y)/(a + 2)

collect the term in w together → ( subtract 2w from both sides)

y - aw - 2w = - 1 → ( subtract y from both sides)

- aw - 2w = - 1 - y → ( multiply through by (- 1) )

aw + 2w = 1 + y → ( take out w as a common factor )

w( a + 2)= 1 + y → ( divide both sides by (a + 2 ) )

w =
(1 + y)/(a + 2)




User Itamar
by
5.0k points